Constituintes fenólicos de ervas e especiarias: um estudo das propriedades antioxidantes e do efeito nos parâmetros físico-químicos de estabilidade do óleo de girassol (Helianthus annuus L.) - Cavalcanti, Cristina Fernandes (2020)
As a contribution to research with natural antioxidants or present work related to the study of the composition of phenolic compounds and the antioxidant capacity of four herbs and spices: rosemary (Rosmarinus officinalis L.), clove (Syzygium aromaticum) or oregano (Origanum vulgare) and curcumin (Curcuma longa L.), in addition to the application of extracts of oxidative protection to sunflower oil, one of the most consumed oils in the world due to its composition of use of greases and natural antioxidants. The ethanolic extracts of the herbs were obtained by cold extraction and subjected to prior evaluation of the antioxidant potential through the determination of the total phenolic content by the Folin-Ciacateau method and evaluation of the antioxidant capacity by the DPPH method. Phenolic compounds were identified and quantified by High Performance Liquid Chromatography (HPLC). Sunflower oil was obtained by cold pressing and the physical-chemical characterization, the fatty acid profile by Gas Chromatography (GC) and Infrared Spectroscopy with Fourier Transform (FTIR) and the profile of tocopherols by HPLC. The thermal stability of the extracts and oil was also evaluated using Thermogravimetry (TG). Oxidative stability was evaluated by Rancimat and PetroOxy and the extracts were applied to the oil at concentrations 100; 200; 500 and 1000 mg.kg-1. The synthetic antioxidant TBHQ was used as a positive control. Sunflower oils added with clove extract and oregano extract (1000 mg. kg-1) were subjected to immersion frying at a temperature of 180 ± 5 °C, controlled by a thermometer, for 90 minutes and samples were analyzed by FTIR. The total phenolic content and DPPH values showed high antioxidant potential for clove extract compared to the other extracts. The HPLC data indicated high concentrations of rosmarinic acid in rosemary and oregano extract, in addition to relevant concentrations of carnosic and caffeic acids. In clove extract the major constituent was eugenol (400 mg. g-1 extract) and curcumin, although not identified, the main constituents were curcuminoids. The extracts showed different thermal profiles by TG, with the clove extract having mass loss above 40% in the first event at the temperature of 55 °C, indicating the thermal degradation of eugenol. The evaluation of the fatty acid profile of the oil indicated 55,5% of linoleic acid and 18% of oleic acid, indicating an oil with more than 70% of its composition in unsaturated fatty acids, which was also confirmed through the infrared spectrum it presented. characteristic regions of unsaturated oils. The tocopherol content was quite high, (205,54 mg. kg-1), with (Fórmula) and γ being identified. Regarding the protective effect of the extracts on the oil, the rosemary extract showed more efficiency in the two techniques evaluated and the turmeric one was the least effective. None of the extracts had a pro-oxidant effect on the oil. In the analysis of the effect of the extracts on the thermal stability of the oil by TG, the extracts of clove and turmeric are not effective, as rosemary and oregano increased the thermal resistance of the oil. In immersion frying analysis, spectra showed that clove and oregano extracts did not provide greater efficiency in delaying oil oxidation during the frying process. However, the correlation between the data evaluated in the present study shows that the use of extracts of these herbs in sunflower oil is feasible, especially considering that the oil without additive has already proved to be quite stable, and the addition of the extracts does not decrease the period of oil induction, even though the extracts had volatile constituents that compromised Rancimat's evaluation.